ANALISIS KONSEP MODUL IPA TERPADU DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA - Atikah Nur Azizah; Hening Widowati; Muhfahroyin Muhfahroyin (BIOLOVA, 2020)
Abstract: The science learning process emphasizes providing direct experience to develop competencies in order to be able to explore and understand the nature around scientifically. students can gain direct experience, so they can add strength to accept and apply the concepts they have learned. Integrated science learning deals with the way students think and develop critical thinking skills. These skills include the ability to think critically, think creatively, and problem solving abilities. Modules are printed teaching materials that are designed to be independently studied by students, Module development is done to improve students' critical thinking skills.